KASUS KEMATIAN AKIBAT DICHLORVOS DAN PHENTHOAT - Nandita, Putu Nandya; Astuti, Ni Made Widi; Wirasuta, IMA Gelgel; Sari, Pande Made Nova Armita (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2019)
Dichlorvos and phenthoat are organophosphate group pesticides which have toxic effects on humans and can cause fatal deaths. Suicide cases using organophosphate pesticides (dichlorvos and phenthoat) are one of the postmortem toxicology analysis studies. As a forensic toxicologist, competency is needed to be able to handle suicide deaths that are thought to be caused by dichlorvos and phenthoat. Handling suicides due to dichlorvos and phenthoate is done from sample preparation, screening tests, assurance tests, determination, and data interpretation. Forensic toxicology analysis in the case showed that high concentrations of dichlorvos and phenthoate were found to have toxic effects on the victim's body. Based on the toxicological analysis, it can be concluded that it is true that the victim died from organophosphate poisoning (dichlorvos and phenthoat).